Structure elucidation and cytotoxic activity of attenuatoside B-1, planciside A, and culcitoside C2 from the starfish Acanthaster planci - Vien, Le Thi; Hong Hanh, Tran Thi; Thanh Huong, Phan Thi; Thao, Do Thi; Thanh, Nguyen Van; Cuong, Nguyen Xuan; Nam, Nguyen Hoai (Vietnam Journal of Science and Technology, 2018)
Detailed analysis of the 1D and 2D NMR data and comparison with the reported values, the structures of attenuatoside B-1 (1), planciside A (2), and culcitoside C2 (3) from starfish Acanthaster planci were clearly elucidated. Culcitoside C2 (3) showed weak cytotoxic activity against five human cancer cell lines including HepG2, KB, LNCaP, MCF7, and SK-Mel2.